2010
DOI: 10.1002/ijc.25302
|View full text |Cite
|
Sign up to set email alerts
|

Imiquimod‐induced clearance of HPV is associated with normalization of immune cell counts in usual type vulvar intraepithelial neoplasia

Abstract: Recently, we reported on the efficacy of imiquimod for treatment of usual type vulvar intraepithelial neoplasia (uVIN). A histologic regression of uVIN to normal tissue was observed in 58% of patients. As success of treatment is related to clearance of high-risk human papilloma virus (HPV), the aim of our study was to assess differences in immune cell counts and in the expression of p16 INK4a in VIN tissue before and after imiquimod treatment, in relation to HPV clearance and clinical response. Vulvar tissue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
79
0
5

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 41 publications
4
79
0
5
Order By: Relevance
“…16 Although there was no significant difference between responding and nonresponding patients, the nonresponding group on average had the highest number of intraepithelial CD141 cells suggesting that these nonresponding patients immunologically were more similar to the recurrent uVIN and vulvar cancer patients. It might be perceived that the intraepithelial CD141 or single CD141 cell population, thus is unfavorable.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…16 Although there was no significant difference between responding and nonresponding patients, the nonresponding group on average had the highest number of intraepithelial CD141 cells suggesting that these nonresponding patients immunologically were more similar to the recurrent uVIN and vulvar cancer patients. It might be perceived that the intraepithelial CD141 or single CD141 cell population, thus is unfavorable.…”
Section: Discussionmentioning
confidence: 83%
“…This is in line with previous studies, the focus of which was mainly on T cell infiltrates and LCs/DCs in uVIN in relation to responses to immunotherapy. 5,7,8,16,17,21,43,44 From these studies it was concluded that the epithelium of uVIN lesions was suppressed as it lacked a strong CD81 infiltration and displayed lower numbers of Langerhans cells. 16,17,21 In contrast, the dermis of uVIN lesions was thought to be the most active region as there was abundant infiltration of CD41 and CD81 T cells as well as mature DCs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations